2005
DOI: 10.1093/brain/awh369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-invasive cortical stimulation on skilled motor function in chronic stroke

Abstract: Stroke is a leading cause of adult motor disability. Despite recent progress, recovery of motor function after stroke is usually incomplete. This double blind, Sham-controlled, crossover study was designed to test the hypothesis that non-invasive stimulation of the motor cortex could improve motor function in the paretic hand of patients with chronic stroke. Hand function was measured using the Jebsen-Taylor Hand Function Test (JTT), a widely used, well validated test for functional motor assessment that refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
764
5
20

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,017 publications
(832 citation statements)
references
References 70 publications
43
764
5
20
Order By: Relevance
“…Several clinical trials involving participants with stroke have also reported highly variable responses (Hummel et al, 2005;Bolognini et al, 2011;Hesse et al, 2011;Khedr et al, 2013). Thus one important future consideration may be to determine which patients with stroke are most likely to benefit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical trials involving participants with stroke have also reported highly variable responses (Hummel et al, 2005;Bolognini et al, 2011;Hesse et al, 2011;Khedr et al, 2013). Thus one important future consideration may be to determine which patients with stroke are most likely to benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a number of approaches are now being investigated in an attempt to increase the effectiveness of stroke rehabilitation techniques for the UE. Non-invasive methods of brain stimulation such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) are extensively researched and are beginning to be used clinically to modulate brain activity (Paulus, 2003;Pascual-Leone et al, 2000;Hummel et al, 2005). Although these two methods have very different modes of action (rTMS stimulates axons in the brain and initiates new action potentials; tDCS polarises the neurones, and modulates their ongoing firing pattern) both of them, when applied over the motor cortex, produce changes in cortical excitability which, in the case of tDCS can last up to 90 min Paulus, 2000, 2001;Fitzgerald et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…tDCS, depending on the polarity, can also enhance (anodal) or suppress (cathodal) excitability of the targeted cortex [43]. Studies have generally downregulated contralesional activity using low-frequency rTMS [44] or cathodal tDCS [45], or upregulated ipsilesional activity using high-frequency rTMS [46] or anodal tDCS [47], or simultaneously applied both [48,49].…”
Section: Are There Other Processes That Can Be Effective To Modulate mentioning
confidence: 99%
“…Les effets ont é té observé s lors des stimulations anodiques du cortex moteur lé sé . La ré alisation d'une stimulation anodique de M1 de la main a mis en é vidence une amé lioration de la force, de la dexté rité et de la vitesse de ré action de la main paré tique (Hummel et al, 2005). L'effet de la tDCS sur les membres infé rieurs se traduit é galement par une augmentation de la force à la suite d'une stimulation anodique (Tanaka et al, 2011).…”
Section: Patients Post Accident Vasculaire Cérébralunclassified